2020
DOI: 10.1161/strokeaha.120.029701
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Potential Solutions of Stroke Care During the Coronavirus Disease 2019 (COVID-19) Outbreak

Abstract: COVID-19 becoming a pandemic as declared by the World Health Organization on March 11, 2020, the world needs to act quickly to have plans ready to deal with the challenges of continuing to deliver high-quality stroke care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
143
3
21

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(171 citation statements)
references
References 4 publications
4
143
3
21
Order By: Relevance
“…For instance, preliminary available data showed that the number of thrombectomies in Shanghai decreased by 50% in the first month after the Spring Festival compared with the same period in 2019. 2 Adverse health outcomes resulting from accessibility barriers posed by the fear of COVID-19 should not be overlooked. Thus, it is necessary to encourage patients to continue seeking emergency care if experiencing acute stroke symptoms.…”
mentioning
confidence: 99%
“…For instance, preliminary available data showed that the number of thrombectomies in Shanghai decreased by 50% in the first month after the Spring Festival compared with the same period in 2019. 2 Adverse health outcomes resulting from accessibility barriers posed by the fear of COVID-19 should not be overlooked. Thus, it is necessary to encourage patients to continue seeking emergency care if experiencing acute stroke symptoms.…”
mentioning
confidence: 99%
“…In the USA, the nine High-Volume catheterization laboratories reported a decrease activation for STelevation myocardial infarction (STEMI) of 38% [7]. The similar trend could be observed by neurologists from China and USA, who reported a dramatic decline of acute strokes of 30-50% [8,9].…”
Section: Introductionmentioning
confidence: 67%
“…The Medscape Medical News also announce a 30% decreased rates of major stroke in Chicago [8]. Furthermore, the preliminary data to Stroke care from Shanghai reported a decrease of thrombectomies by 50% in the rst month after the Spring Festival (24th to 30th January 2020) [9]. Those specialties discussed the reduction of stress and the deceleration of public live as a potential reason for such a decline of cardiovascular emergencies [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, no parece que se generen cambios ni en la exploración clínica ni en las indicaciones de exploraciones complementarias, al menos por el especialista de Neurologia. Tampoco los informadores clave consideran que haya cambios en el desarrollo de las unidades de ictus, aunque puedan haber circuitos específicos para pacientes que resulten covid+ (30,31) . Los encuestados también señalan que la pandemia conllevará nuevas formas de funcionamiento de los congresos, así como la asistencia de monitores de los ensayos clínicos y la utilización progresiva de medios electrónicos en sustitución del papel.…”
Section: Discussionunclassified